Standarisasi Content Creator dalam Mengemas Postingan di Media Sosial Instagram - Rayinda Aliya Ikhtiyar; Raditya Pratama Putra (UNISBA Press, 2024)
Abstract. In the current era of disruption, new professions have emerged in the digital media landscape, including the rise of content creators. This profession involves the creation of various content types such as text, images, audio, video, or other visual combinations tailored for digital media and distribution across social platforms. Utilizing social media platforms for personal branding has become a means of self-existence, as exemplified by Rofie Fauzie, a content creator. The research problem formulated in this study is